Students perceptions towards spiritual practice in learning process / Tengku Mardhiah Tengku Jalal, Fadila Amira Razali and Nor Hidayah Hassim - Tengku Jalal, Tengku Mardhiah; Razali, Fadila Amira; Hassim, Nor Hidayah (2016)
From Islamic perspectives, spirituality is one of the important factors towards the individual achievements. This is because individuals with good spiritual practice will have a good attitude in every aspect including their attitude towards study. Therefore this study was conducted to identify relationship between perception towards spiritual approach and spiritual practices. In addition, relationship between spiritual practice and academic achievement was also examined. This study also was wishes to investigate the relationship between perception towards spiritual approach and academic achievement. A cross sectional study was conducted among students in UiTM Cawangan Pahang Kampus Raub. Sample of 108 respondents were selected randomly using Simple Random Sampling Technique where each respondents have to answer a set of questionnaire. Results showed that a significant positive relationship was observed between the spiritual practice and the perception towards spiritual approach. However, there were no significant relationship could be conclude between the spiritual practice among students and their academic achievement. The relationship between the perception towards spiritual approach and academic achievement were also has no significant correlation. As a conclusion, the applications of spiritual practices among students in UiTM Cawangan Pahang Kampus Raub were related to their perception of spiritual approach. In order to generate students with good spiritual practices, their perception towards the effect and important of spiritual practices in improving their academic achievement should be strengthened.